2020
DOI: 10.1186/s12913-020-4918-z
|View full text |Cite
|
Sign up to set email alerts
|

“Navigation to prioritizing the patient” – first-line nurse managers’ experiences of participating in a quality improvement collaborative

Abstract: Background: First-line nurse managers are central to quality improvement work when changing work practices into better patient outcomes. Quality improvement collaboratives have been adopted widely to support quality management in healthcare services and shared learning. We have little knowledge of the first-line nurse managers' own perspectives concerning their need for support and knowledge in quality improvement work. Therefore, the aim of this study was to gain understanding of first line nurse managers' ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Multiple studies have identified a positive link between the relational leadership style and nurses' job satisfaction [3,6,40], while other research has linked this leadership approach with patient satisfaction [2,3,41]. In addition, it is challenging for nurse managers to lead quality improvement in the complex everday environment of a health care organization [42]. Recent studies have shown that leadership, managerial support and nurse-manager trust reduce medication errors and increase both patient safety culture and the quality of care [5,6,43].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have identified a positive link between the relational leadership style and nurses' job satisfaction [3,6,40], while other research has linked this leadership approach with patient satisfaction [2,3,41]. In addition, it is challenging for nurse managers to lead quality improvement in the complex everday environment of a health care organization [42]. Recent studies have shown that leadership, managerial support and nurse-manager trust reduce medication errors and increase both patient safety culture and the quality of care [5,6,43].…”
Section: Introductionmentioning
confidence: 99%
“…The literature highlights the important role of leaders in improving collaboration (Lemetti et al, 2015). According to Sjølie et al (2020), first-line nursing managers are essential for improving the quality of care; they are able to change work practices, which leads to better outcomes for patients. However, in our context, the assistance units are physically far from the management ones (Guzmán-Fernández, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These daily adaptations and resource restrictions affected the way that managers prioritise the ordinary operations of services and integrate quality and safety improvement activities. A recent qualitative study of front-line nurse managers found that both a lack of time for quality improvement work and a lack of time generally when several problems needed to be solved led to hasty solutions and not permanent improvement work in nursing homes and homecare services (Sjølie et al, 2020). Our study co-designed an intervention that was contextually sensitive to the challenges facing managers in their daily work, their risk picture and also in terms of where they were performing well (Paper I).…”
Section: Multiple Challenges In Quality and Safety Workmentioning
confidence: 99%
“…Boundary objects can also promote knowledge sharing and transfer within groups and facilitate learning (Kanwal et al 2019). In healthcare settings, boundary objects are often used to improve interprofessional collaboration (Engstrøm et al, 2005;Keshet et al, 2013;Sjølie et al, 2020;Wiig et al, 2014b).…”
Section: The Leadership Guide As a Boundary Object For Managers In Qu...mentioning
confidence: 99%